Traditional morality and the depiction of non muslims in Islamic studies an analytical account - Ramdane, Tahraoui; Souad, Merah (2019)
This conceptual paper aims to highlight the traditional morality and the conventional depiction of non- Muslims in the Islamic Studies rhetoric and its influence in shaping stereotypes on the “Other”. A Literature review was conducted via a reflective analysis in which ideas grouping was made and recommendations were deducted. The findings have revealed that the Islamic studies rhetoric is still conventional. It emphasizes on religious rituals and little effort was put in fostering values of understanding and co-existing with the “Other”. It is expected that the results of this study will help in clarifying the need for a language of tolerance and moderation to be adopted in addressing the “other” (non- Muslims and non-Sunni) in order to reduce the gap between religions, and to prepare young Muslims living and working in harmony with humanity at large.